PERBANDINGAN PENGARUH ANTARA LATIHAN MOTORIK DENGAN NIR-MOTORIK TERHADAP TENDANGAN PENALTI DALAM PERMAINAN SEPAK BOLA - Subekti, nuriska (Universitas Negeri Semarang, 2017)
The purpose of this study was to determine the effect of motor and non-motor training on penalty kicks in the game of soccer and to know the most effective exercise between the two exercises. The method of this research is experimental method. The population of this research is the students of Siliwangi University of Tasikmalaya who participated in the activity of football SMEs as many as 30 people. From the entire population taken as many as 30 people to be sampled in this study by using the total sampling technique. Based on the results of data processing and data analysis the authors can conclude that the exercise motor and non-motoric significantly effect on penalty kicks in soccer games on football SMEs Siliwangi University Tasikmalaya. Both exercises are equally effective, because based on the results of data processing there is no difference in the increase in exercise results between the two groups of training. Based on the results of the study, the authors suggest that teachers and coaches should always pay attention to basic techniques especially penalty kicks because penalty kicks in the game of football is one of the key determinants of victory. Exercises that can be used in an effort to increase the ability to do this penalty kick Is a motor exercise that is supplemented by non-motor training. Therefore, both exercises should be taken into consideration in order to choose the method of training to improve the skill of penalty kicks, so that the exercise is not done in vain.